The impact of hip-spine relations on the results of total hip arthroplasty (literature review) - Korzh, Mykola; Radchenko, Volodymyr; Filipenko, Volodymyr; Popsuishapka, Kostiantyn; Pidgaiska, Olga (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
Spine balance can alter THA outcomes, but the exact mechanism is not yet well recognized. We aimed at bridging the gap between hip and spine surgeons with an up-to-date analysis of the best available literature review concerning to data as for total hip arthroplasty results of those patient with concomitant spine disorders. In total hip arthroplasty accurate acetabular cup placement is essential for impingement free and stable range of motion. For decades, hip surgeons have relied on traditional safe acetabular zones to reduce prosthetic instability. Nevertheless, hip dislocation is one of the most common complications following total hip arthroplasty. Numerous studies have shown that patients with abnormal spinopelvic mobility due to degenerative spinal diseases and after spinal fusion surgery had an increased rate of dislocations after THA. In our review we described the main spine-pelvic parameters, such as pelvic tilt, sacral slope, pelvic incidence, lumbar lordosis etc. and spino-pelvic motions and how they can change in standing and sitting postures. Measurements of these parameters are necessary for presurgical planning before hip arthroplasty especially those patients who had previously made spine fusion. A review of literature shows that sagittal pelvic kinematics, but not the pelvic incidence, influences the risk of prosthetic impingement or dislocation. Pelvic position is dynamic during gait and other daily living activities. Variations in anteroposterior pelvic tilt affects the resulting spatial orientation of the acetabulum. Recommendations for cup positioning are switching from a classic Lewinneck safe zone to a patient-specific approach, with the standing cup orientation giving way to a new parameter of interest: the functional orientation of the cup. Thus, functional cup anterversion should be taken into consideration. Abnormal spinopelvic mobility is a risk factor for THA dislocation. Thus patients with combined spine and hip pathology are at higher risk for further complications and they should be identified and screened more carefully. Key words. Spine-pelvic relations, sagittal alingement, hip arthroplasty, dislocation